How healthy and food secure is the urban food environment in Ghana?. (June 2022) - Mockshell, Jonathan; Ogutu, Sylvester O.; Álvarez, Diego; Asante-Addo, Collins; Asante, Felix A.
Highlights: Urban food environments in developing countries have received little attention. We conduct a macro-scan of the urban food environment in Ghana. Results show that processed foods contribute to the larger share of all foods. Ultra-processed foods comprise more than 30% of all processed foods. Policy options to nudge the food environment to deliver healthy foods are discussed. Abstract: The importance of the food environment in influencing dietary choices of consumers has been widely acknowledged, but little attention has been paid to the urban food environment in Africa despite the rise in incidence of obesity and other nutrition-related noncommunicable diseases (NR-NCDs). We contribute to the literature on urban food environments by conducting an observational macro-scan of the food environment in three cities – Accra, Cape Coast, and Koforidua – with a view to unravelling the nature of the urban food environment in Ghana. We examine the food environment based on two dimensions of food security – availability and accessibility (affordability) – and also assess the extent to which foods are processed. The results show that all four food categories – unprocessed, processed, processed culinary, and ultra-processed – are available, accessible, and affordable. Ultra-processed foods are just as highly available, accessible, and/or affordable as unprocessed foods. The results also show that processed foods account for the larger share of all foods in Ghana's urban food environment, and ultra-processed foods account for more than 30% of all processed foods. Overall, these results suggest that physical and economic access to food are not major constraints in urban Ghana. This is certainly a welcome finding from a food policy perspective; however, the high availability and accessibility of ultra-processed foods has serious potential health implications. Regulation will be needed to prevent overconsumption of ultra-processed foods and the resulting increase in obesity and other NR-NCDs.